Podkhody k razrabotke konzeptsii individualizatsii podgotovki sportsmenov vysokoi kvalifikatsii - Rybakov, V. V.; Medvedeva, G. E.; Aleshin, I. N.; Sidorov, A. D. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
The article concerns around the approaches to elaboration of the concept of individualization in elite athletes training. According to the authors' opinion, the efficiency of athletes training depends in high grade on the unity of training and contests structures. On the base of experimental data, it is possible to concretize the scientific apprehensions about individual factors of sports mastership developing. The system of pedagogical mistakes minimization presented in article can provide the higher efficiency of an individual training process.